2020
DOI: 10.2106/jbjs.20.00788
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Aseptic Loosening After Total Knee Arthroplasty with a Rotating-Hinge Implant

Abstract: Background: Successful results have been reported in association with the use of a rotating-hinge prosthesis for primary total knee arthroplasty (TKA). The objective of the present study was to identify risk factors for aseptic loosening in patients who underwent primary TKA with rotating-hinge knee prostheses. Methods: The records of 1,235 patients who underwent primary TKA with a rotating-hinge prosthesis at our center were evaluated. A total of 125 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Approximately 20% of patients undergone manual TKA may complain of their clinical outcomes, and more than 6% of patients who underwent primary TKA need revision 5,33,34 . Successful TKA require an understanding of case‐specific anatomy and meticulous techniques to protect soft tissue, preserve joint balance, rebuild the mechanical axis and obtain range of motion 35,36 . The implementation of TKA is subject to technical thresholds and errors that potentially lead to joint instability, loosening or persistent pain 37–39 .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20% of patients undergone manual TKA may complain of their clinical outcomes, and more than 6% of patients who underwent primary TKA need revision 5,33,34 . Successful TKA require an understanding of case‐specific anatomy and meticulous techniques to protect soft tissue, preserve joint balance, rebuild the mechanical axis and obtain range of motion 35,36 . The implementation of TKA is subject to technical thresholds and errors that potentially lead to joint instability, loosening or persistent pain 37–39 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the PJI diagnosis, all patients were diagnosed according to the standard pre-operative protocol of ENDO-Klinik [2] and the definition of PJI was made according to the first ICM criteria [3], as asked by Aliyev et alCorresponding to the second concern that the cement mantle thickness or the ratio of stem diameter to femoral canal diameter might be an independent risk factor is in general good aspects. In our previous study [4], aseptic loosening (AL) was significantly found higher in patients with a wider femoral inner diaphyseal parameter even in the in the setting of primary rotating hinge implants without any bone loss. In both studies [1,4], the ROKNEP Endo-Model (Waldemar…”
mentioning
confidence: 81%
“…In our previous study [4], aseptic loosening (AL) was significantly found higher in patients with a wider femoral inner diaphyseal parameter even in the in the setting of primary rotating hinge implants without any bone loss. In both studies [1,4], the ROKNEP Endo-Model (Waldemar…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Subsequently, the novel radiological classi cation system, also known as Citak Classi cation, was introduced to the literature [5]. The Citak Classi cation divides the distal femur into three groups, where the population with a wider inner diaphyseal diameter is represented by type C with the highest risk for AL of the femoral component [9]. In this context, we aimed to identify anatomical variants of the proximal tibia shaft to develop a novel classi cation system for proximal tibia.…”
Section: Introductionmentioning
confidence: 99%